Do cárcere à cena : corpos atravessados na dança performativa Para Menores - Victorino, Elka Moura (2019)
Is it possible to construct a poetic dance / performance from the encounter between a ballerina's body and the bodies of imprisoned youth? Considering that the body, in contemporary dance and performance is the place where actions are engendered for the scene, this study discusses the issues that involved the performative dance creation process. Reflects on the memories of a conflict experience as a dance teacher at the Cuiabá Socio-Educational Center (CASE-MT), which triggered the process of creating the scenic event and writing. Cartography as thought by Deleuze and Guattari and expanded by Sueli Rolnik was adopted as a methodological resource, as it is closer to contemporary artistic poetics. Reality and fiction, art and life, theory and practice intertwinedwith each other. Theorists like Michel Foucault, docile bodies; José Gil, paradoxical body; Larrosa, experience; Doubrovsy, self-fiction and Halbwachs, memory supported the construction of a map of perceptions, movements, scenes gestures, intensities of the record of this work. After traversing countless paths to the spelling of text and dance, it is clear that a poetics in contemporary dance can be built from the memories of a relationship of affection between bodies that, at the same time, were strangely recognized and recognized within each other. a system called "socioeducation".